2015
DOI: 10.3390/cancers7010305
|View full text |Cite
|
Sign up to set email alerts
|

Immunreconstitution and Infectious Complications After Rituximab Treatment in Children and Adolescents: What Do We Know and What Can We Learn from Adults?

Abstract: Rituximab, an anti CD20 monoclonal antibody, is widely used in the treatment of B-cell malignancies in adults and increasingly in pediatric patients. By depleting B-cells, rituximab interferes with humoral immunity. This review provides a comprehensive overview of immune reconstitution and infectious complications after rituximab treatment in children and adolescents. Immune reconstitution starts usually after six months with recovery to normal between nine to twelve months. Extended rituximab treatment result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 95 publications
2
51
1
Order By: Relevance
“…Hypogammaglobulinemia has been reported with chronic use of rituximab but mostly in patients with hematological malignancies. The incidence of hypogammaglobulinemia can range from 20 to 50% in patients treated for lymphoma [ 20 ] but is much lower in RA and ANCA-associated vasculitis (4% and 4.2%, respectively) [ 17 , 21 ]. A similar low incidence of 3% has been reported in MS patients by Salzer et al [ 11 ], but the drop in the aggregate serum IgG levels was slight.…”
Section: Discussionmentioning
confidence: 99%
“…Hypogammaglobulinemia has been reported with chronic use of rituximab but mostly in patients with hematological malignancies. The incidence of hypogammaglobulinemia can range from 20 to 50% in patients treated for lymphoma [ 20 ] but is much lower in RA and ANCA-associated vasculitis (4% and 4.2%, respectively) [ 17 , 21 ]. A similar low incidence of 3% has been reported in MS patients by Salzer et al [ 11 ], but the drop in the aggregate serum IgG levels was slight.…”
Section: Discussionmentioning
confidence: 99%
“…Hypogammaglobulinemia has been reported with chronic use of rituximab but mostly in patients with hematological malignancies. The incidence of hypogammaglobulinemia can range from 20 to 50% in patients treated for lymphoma [20] but is much lower in RA and ANCA-associated vasculitis (4% and 4.2%, respectively) [17,21]. A similar low incidence of 3% has been reported in MS patients by Salzer et al [11], but the drop in the aggregate serum IgG levels was slight.…”
Section: Discussionmentioning
confidence: 57%
“…In this regards, reports showed that RTX treatment is associated with immune reconstitution and B-cells recovery, which usually starts 6 months after therapy with complete recovery to normal levels in 9-12 months. 30 Moreover, it was also demonstrated that patients who receive extended RTX treatment showed no evidence of increasing clinically relevant infection. 30 Our study adds support to the concept of using this drug for extended time.…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, it was also demonstrated that patients who receive extended RTX treatment showed no evidence of increasing clinically relevant infection. 30 Our study adds support to the concept of using this drug for extended time. This approach might help in the adoption of novel management strategies with the aim of sufficiently administrating RTX far enough in advances to prevent disease progression or relapse.…”
Section: Discussionmentioning
confidence: 99%